P77 Use of the new south west chest X-ray reporting tool (SW CXR RT) to assist implementation of the national optimal lung cancer pathway (NOLCP). (12th November 2019) - Pearce, C; Alaee, S; Sugden, P; Foster, S; Steer, H; Hall, T; Masani, V
Abstract : Introduction and objectives: The National Optimal Lung Cancer Pathway (NOLCP) recommends 'reflex' CT scans for patients whose chest X-rays (CXRs) identify changes suggestive of lung cancer. It is recommended that a CT scan is performed on the same day of the CXR or within 72 hours. The Southwest Lung Cancer Alliance introduced the 'Southwest chest X-ray reporting tool' (SW CXR RT) to help identify patients requiring reflex CT scans, and therefore streamline the first part of the NOLCP. The SW CXR RT identifies 3 categories; CX1 (normal CXR), CX2 (abnormal pathology of uncertain significance), CX3 (CXR highly suggestive of lung cancer). We audited the efficacy of using the SW CXR RT in identifying patients with a new diagnosis of lung cancer, subsequently managed via the NOLCP. Methods: Results from 3 Trusts were collated over an 8 month period (1st June 2018–31st January 2019). The diagnoses of patients with CX3 reports and subsequent reflex CT scans were reviewed. Results: 448 patients underwent CXRs with subsequent CX3 reports; all of whom subsequently had reflex CT scans. The 448 reflex CT scans identified the following diagnoses: 153 (34%) newly diagnosed of lung cancers, 28 (6%) non-cancer thoracic malignancy, 61 (14%) community acquired pneumonia, and 206 (46%) other diagnoses. 153 patients with newly diagnosed lung cancer were classified as follows; 52 (34%) adenocarcinoma, 28 (18%) squamous cell, 15 (10%) other non-small cell cancer, 14 (9%) small cell cancer, 34 (22%) clinico-radiologically diagnosed with lung cancer, 10 (7%) with lung metastases. In total 153/448 (34%) patients receiving a reflex CT scan were subsequently diagnosed with lung cancer; and 181/448 (40%) were diagnosed with a malignant condition. Conclusions: Introduction of the SW CXR RT helped facilitate reflex CT scanning, with 40% of patients subsequently diagnosed with a malignant condition. The true positive rate for malignancy in patients with CX3 reports was less than anticipated. Subjectively, radiologists differ in their threshold for scoring a CXR as CX3. Further work should audit CX3 reporting and ongoing feedback to radiologists should improve the rate of true positives in this group.